La situación del tororoi pechicanela (grallaria haplonota, formicariidae) en colombia (1995)
We present the first specimen records of Grallaria haplonota for Colombia, where it occurs between 1300 and 1700 m long the Pacific slope of the western Andes, north to Risaralda. Data on the ecology and vocalizations are presented, as well as a brief discussion of taxonomic problems in the species.